2008
DOI: 10.3122/jabfm.2008.02.070158
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudes Toward Early Abortion Services in the Family Medicine Clinic

Abstract: Purpose: To examine urban, inner-city female patients' acceptability of the provision of early abortion services by their family physician in the family medicine clinic (FMC).Methods: We administered a survey with open-and closed-ended questions to a convenience sample of English-or Spanish-speaking female patients aged 18 to 45 recruited from a FMC in the Bronx, New York. Responses were analyzed using quantitative and qualitative methods.Results: One hundred forty-eight women completed the survey. The majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Indeed, our findings suggest that urban women, and particularly those of higher socioeconomic status, have stronger desires for autonomy and privacy in their reproductive decision-making than their rural and lower socioeconomic status counterparts. Indeed, preferences from these subgroups in our Indian sample echo those articulated among women in New York City and Romania (Johnson et al, 1996;Rubin et al, 2008). Surprisingly, we found very few differences in women's assessments of the importance of provider attributes based on their abortion history.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, our findings suggest that urban women, and particularly those of higher socioeconomic status, have stronger desires for autonomy and privacy in their reproductive decision-making than their rural and lower socioeconomic status counterparts. Indeed, preferences from these subgroups in our Indian sample echo those articulated among women in New York City and Romania (Johnson et al, 1996;Rubin et al, 2008). Surprisingly, we found very few differences in women's assessments of the importance of provider attributes based on their abortion history.…”
Section: Discussionsupporting
confidence: 54%
“…One study examined the acceptability of provision of abortions by family physicians among a convenience sample of women attending a family medicine clinic in New York City. Among the 90 women who said they would consider having an abortion, 73% said they would have their family physician perform it, while 22% said they would choose to have it in a large abortion clinic, and 5% had no preference (Rubin, Godfrey, & Gold, 2008). Only two studies have asked women specifically about the attributes of providers they value.…”
Section: Preferences For Abortion Providersmentioning
confidence: 95%
“…As a result, many are calling for the integration of early abortion into primary care settings [25,26], which for many students is an on-campus SHC. Studies have shown that women would prefer to receive abortion services at their primary care facility, because they feel connected to the setting, trust their provider, find it more convenient, and seek continuity of care [8,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, one survey found that the majority of family medicine clinic patients who would consider using abortion services would prefer to receive them at their primary care clinic rather than visit a freestanding, high-volume abortion clinic. 10 The steps involved in procedural abortion are (1) counseling and evaluation before the procedure, including selection of pain control methods; (2) offering appropriate analgesia and/or anesthesia; (3) achieving adequate cervical dilation; and (4) complete aspiration of uterine contents. If the clinician is certain that the abortion is complete and if the patient chooses to initiate her contraceptive method at that visit, no follow-up appointment is needed.…”
mentioning
confidence: 99%